Controlling IT Outsourcing Risks in the European Union Banking Sector : Common Practices and Potential Challenges - Österholm, Jon Erik Alexander (My University, 2025)
This thesis investigates the risk management practices associated with IT outsourcing in the European Union's banking sector and the rapidly evolving digital landscape. Through qualitative analysis, including interviews with industry professionals, the study identifies key strategies for mitigating risks related to IT outsourcing. These risks include over-reliance on individual suppliers, regulatory compliance challenges, and the need for contingency planning. The study highlights the importance of regulatory frameworks in standardizing outsourcing practices and improving resilience. The data collected from the interviews were analyzed using thematic narrative analysis to identify trends, similarities, or contradictions in the responses, leading to conclusions on effective methods for managing IT outsourcing risks in the European Union’s banking sector. Five industry professionals were interviewed, chosen for their professional expertise in the European financial sector, particularly in IT outsourcing procedures and risk management practices. The findings highlight the critical role of well-structured contracts and a skilled IT workforce in mitigating IT outsourcing risks. Effective contracts should clearly define service level agreements (SLAs), liability clauses, and exit strategies to ensure both parties are protected, and obligations are met. Additionally, the study underscores the need for continuous monitoring and evaluation of outsourcing partners to maintain compliance and performance standards. The research also points out the significance of due diligence in the partner selection process. Banks must thoroughly assess potential vendors' capabilities, financial stability, and compliance with regulatory requirements. Certification and adherence to industry standards are crucial in ensuring that vendors can meet the stringent demands of the banking sector. Furthermore, the study suggests that future research could explore the impact of workforce competencies on the outsourcing strategies of banks. As the digital landscape continues to evolve, the ability to attract and retain skilled IT professionals will be vital in managing outsourcing risks effectively. By offering insights into the current state of IT outsourcing risk mitigation in the European banking sector, this thesis contributes to the understanding of how banks can better navigate the complexities of digital transformation while ensuring stability, compliance, and competitive advantage in the digital era.

Tässä tutkimuksessa tarkastellaan tietotekniikan ulkoistamisen riskienhallintakäytäntöjä nopeasti kehittyvässä digitaalisessa ympäristössä Euroopan unionin pankkisektorilla. Laadullisen analyysin ja alan ammattilaisten haastattelujen avulla tutkimuksessa selvitetään strategioita IT-ulkoistamisriskien hallintaan. Näihin riskeihin kuuluvat liiallinen riippuvuus yksittäisistä toimittajista, sääntelyn noudattamiseen liittyvät haasteet ja irtautumisstrategioiden tarve. Irtautumisstrategialla viitataan tilanteeseen, jossa pankki joutuisi nopeasti irtaantumaan IT-ulkoistussuhteesta. Lisäksi tutkimuksessa korostetaan sääntelykehysten merkitystä ulkoistamiskäytäntöjen standardoinnissa ja häiriönsietokyvyn parantamisessa. Haastatteluista kerätty aineisto analysoitiin temaattisen narratiivianalyysin avulla, jotta voitiin tunnistaa trendit, yhtäläisyydet tai ristiriidat vastauksissa. Viisi alan ammattilaista valittiin haastateltaviksi heidän asiantuntemuksensa perusteella Euroopan unionin rahoitussektorilla, erityisesti IT-ulkoistamisprojekteista ja riskienhallintakäytännöistä. Analyysin avulla tehtiin johtopäätöksiä tehokkaista menetelmistä IT-ulkoistamisen riskien hallintaan Euroopan unionin pankkisektorilla. Analyysin tulokset korostavat selkeästi rakennetujen sopimusten ja osaavan IT-henkilöstön kriittistä roolia IT-ulkoistamisen riskien hallinnassa. Tehokkaiden sopimusten tulisi selkeästi määritellä palvelutasosopimukset (SLA), vastuulausekkeet ja irtautumisstrategiat, jotta velvoitteet täytetään ja riskit vähenevät. Lisäksi tutkimus painottaa ulkoistamiskumppaneiden jatkuvan seurannan ja arvioinnin tarvetta sääntelyn noudattamisen ja suorituskyvyn standardien ylläpitämiseksi. Ulkoistamiskumppanin valintaprosessia korostettiin kriittiseksi osaksi riskienhallintaa. Pankkien on arvioitava perusteellisesti potentiaalisten toimittajien kyvykkyydet, taloudellinen vakaus ja sääntelyn noudattaminen. Sertifioinnit ja alan standardien noudattaminen ovat tärkeitä keinoja, joilla toimittajat voivat täyttää Euroopan pankkisektorin tiukat vaatimukset. Tutkimuksessa ehdotetaan, että jatkotutkimuksissa voitaisiin tarkastella tietotekniikka-alan ammattilaisten vaikutusta pankkien tietotekniikan ulkoistamisriskien hallintaan. Tutkimus voisi pyrkiä ymmärtämään mahdollisia riskejä, joita pankkien IT-henkilöstön osaamistasoon liittyy ja miten tätä voisi mitata. Digitaalisen ympäristön kehittyessä kyky houkutella ja pitää palveluksessaan ammattitaitoisia IT-ammattilaisia on ratkaisevan tärkeää ulkoistamisriskien tehokkaan hallinnan kannalta. Tarjoamalla tietoa IT-ulkoistamisen riskienhallinnan nykytilasta Euroopan pankkialalla tämä tutkielma edistää osaltaan sen ymmärtämistä, miten pankit voivat paremmin selviytyä digitaalisen muutoksen monimutkaisista haasteista varmistaen samalla sääntelyn noudattamisen digitaalisella aikakaudella.
Keywords: risk management; outsourcing; banking sector; information technology; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business